EFFECT OF LEAD AND CADMIUM ON GROWTH OF MEDICAGO SATIVA L. AND THEIR TRANSFER TO FOOD CHAIN - S. Aslam; F. Sharif; A. U. Khan (Journal of Animal and Plant Sciences, 2015)
Lead and cadmium are considered potential hazards for being most common pollutants in our environments. Current study was conducted at Government College University Botanic Garden, Lahore to examine the effects of Pb and Cd on different growth parameters of a major fodder crop Medicago sativa, and their transfer to a herbivore (rabbit). Plants were grown under field conditions with different treatments prepared as, control (T0), Pb 200 µg/g soil (T1), Pb 400 µg/g soil (T2), Cd 4 µg/g soil (T3), Cd 8 µg/g soil (T4), Pb 200 µg/g soil + Cd 4 µg/g soil (T5) and Pb 400 µg/g soil + Cd 8 µg/g soil (T6), each in triplicate and in a completely randomized design. After harvest, rabbits (Oryctolagus cuniculus) were fed with the plant tissues of all treatments for ten days. Significant (P < 0.05) reduction was observed in growth parameters of the plants with increase in metal levels both in single and combined treatments. The maximum accumulation of Pb (96%) and Cd (89%) was observed in roots while the highest translocation of Pb and Cd to shoots was 38 and 37%, respectively. Faeces of rabbits showed much higher values of Pb and Cd than blood samples as about 65% Pb and 38% Cd was excreted via faeces. Overall, results of the study show that M. sativa has the ability to retain maximum concentrations of Pb and Cd in roots and restricts their translocation to shoot and leaves. So the risk of transfer of toxic amounts of Pb and Cd to human beings through this route seems low.
Keywords: Lead; cadmium; soil; alfalfa; rabbit; food chain